Penerapan Etika Pelayanan Customer Service pada Bank Tabungan Negara Syariah Tagerang - Didi Suardi; Dila Pebriyanti (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2023)
This research critically examines the implementation of customer service ethics at Bank Tabungan Negara KCS Tangerang using a qualitative descriptive approach. The study aims to shed light on the ethical practices adopted by customer service representatives while interacting with clients. Data for this investigation was collected through primary and secondary sources. Primary data was derived from observations and structured interviews with key informants, including the Service Quality Unit at Bank Tabungan Negara KCS, supporting informants from the bank's clientele, and expert professionals. On the other hand, secondary data was acquired from pertinent articles, brochures, standard operating procedures (SOPs), reputable journals, theses, books, and related documentation. The research findings illuminate the commendable application of ethical principles by customer service representatives when attending to clients at Bank Tabungan Negara KCS Tangerang. The observed ethical practices encompass positive attitudes and behaviors, presentable appearance through the utilization of appropriate uniforms and name tags, polite and informative communication, skillful use of questioning techniques, and the exhibition of courteous body language during customer interactions. The results of this study contribute to our understanding of ethical customer service practices within the banking sector and highlight the significance of ethical conduct in cultivating a positive and satisfactory customer experience. Additionally, the findings underscore the role of customer service ethics in building and maintaining a favorable reputation for the bank in the eyes of its clients.